Rhythmic ictal nonclonic hand (RINCH) motions in temporal lobe epilepsy: invasive EEG findings, incidence, and lateralizing value - Kuba, Robert; Musilová, Klára; Vojvodič, Nikola; Tyrlíková, Ivana; Rektor, Ivan; Brázdil, Milan (Epilepsy research, 2013)
The main purpose of this retrospective analysis was to evaluate the incidence and lateralization value of rhythmic ictal nonclonic hand (RINCH) motions in patients with temporal lobe epilepsy (TLE), who were classified as Engel I at least 2 years after epilepsy surgery. We analyzed the distribution of ictal activity at the time of RINCH appearance in patients in whom RINCH motions were present during invasive EEG monitoring. A group of 120 patients was included in this study. In total, we reviewed 491 seizures: 277 seizures in patients with temporal lobe epilepsy (TLE) associated with hippocampal sclerosis (TLE-HS group) and 214 in TLE caused by other lesions (TLE-OTH group). We analyzed 29 patients (79 of the seizures) during invasive EEG monitoring. Fisher's exact test and binomial test were used for the statistical analysis. RINCH motions were observed in 24 out of 120 patients (20%) and in 48 out of 491 seizures (9.8%). There was no significant difference between the occurrence of RINCH motions in patients with TLE-HS and in patients with TLE-OTH, or between gender, right/left-sided TLE, and language dominant/nondominant TLE. RINCH motions were contralateral to the seizure onset in 83.3% of patients and 91.7% of seizures (p=0.0015; p<0.001, respectively). There were no differences in the lateralizing value of RINCH motions in patients with TLE-HS or TLE-OTH. We analyzed RINCH motions in 5 patients/7 seizures during invasive EEG. In all 7 seizures with RINCH motions, we observed the widespread activation of the temporal lobe (mesial and lateral, opercular and polar regions) contralateral to the side of RINCH motions. In all 7 seizures, we observed that at the time of RINCH motion onset, at least 1 explored region of the frontal lobe was affected by the ictal activity. In 3 seizures, we observed time-locked epileptic activation associated with the appearance of RINCH motions, i.e., in the orbitofrontal cortex in 2 seizures and in both the orbitofrontal cortex and anterior cingulate gyrus in 1 seizure. RINCH motions are a relatively frequent ictal sign in patients with TLE. They have a high lateralizing value in these patients, occurring contralateral to the ictal onset. RINCH motions usually occur after the spread of ictal activity beyond the temporal lobe, and their appearance is usually associated with the presence of ictal activity in various regions of the contralateral frontal lobe, mainly the orbitofrontal cortex and anterior cingulate gyrus. This is the first study analysing this phenomenon during invasive EEG recording.
Keywords: dospělí; mozek; ruka; retrospektivní studie; Brain; Epilepsy, Temporal Lobe; Humans; lidé středního věku; Middle Aged; Young Adult; Functional Laterality; epilepsie temporálního laloku; mladý dospělý; elektroencefalografie; incidence; mužské pohlaví; Hand; funkční lateralita; Adult; Adolescent; Electroencephalography; pohybové poruchy; ženské pohlaví; Brain Neoplasms; nádory mozku; Movement Disorders; lidé; mladiství; dítě; Child; Incidence; Male; Retrospective Studies; Female